Floristic composition and vegetation community analysis of Gesha and Sayilem Forest in Kaffa Zone south western Ethiopia - Admassu Addi; Teshome Soromessa; Tura Bareke (Society for Indonesian Biodiversity, 2020)
Abstract. Addi A, Soromessa T, Bareke T. 2020. Plant diversity and community analysis of Gesha and Sayilem Forest in Kaffa Zone, southwestern Ethiopia. Biodiversitas 21: 2878-2888. The study was conducted at Gesha and Sayilem districts of the Kaffa Zone with the objective of identifying the floristic compositions, plant community types, and associated environmental factors of the forest. Stratified random sampling technique was used. A total of 90 plots were used to collect vegetation data. The plant community classification was performed using agglomerative Hierarchical cluster analysis Ward’s linkage method was applied in R-software. Species diversity and evenness were evaluated using the Shannon diversity and evenness indices respectively. The study revealed that the study area composed of 300 species that belong to 239 genera in 96 families. Asteraceae was the most abundant family followed by Fabaceae, Acanthaceae, Poaceae, Rubiaceae, and Euphorbiaceae accounting 37%, 15%, 14%, 13%, 12%, and 9% respectively. Five plant community types were identified and these were Ilex mitis-Syzygium guineense, Pouteria adolfi-friedericii-Schefflera abyssinica, Millettia ferruginea-Sapium ellipticum, Arundinaria alpina and Schefflera volkensii-Masea-lanceolata community types. Among the community types, Pouteria adolfi-friedericii-Syzygium guineense community was the most diverse whereas Arundinaria alpina community was the least diverse community. Canonical Correspondence of vegetation data analysis indicated that altitude, disturbance, slope, phosphorus, and the electrical conductivity were the environmental factors that significantly influence the plant communities. The high dependency of local communities on the forest resources is affecting the plant biodiversity. Thus, conservation of the forest through the introduction of sustainable forest management interventions including participatory forest management seems an appropriate action.